Impact of e-Commerce Adoption on Marketing Performance - Sugandini, Dyah; Suwardi, Suwardi; Ghofar, Abdul (RSF Conference Series: Business, Management and Social Sciences, 2021)
This review plans to examine the impact of relative advantage, perceived ease of use, and perceived usefulness on the marketing performance of SMEs mediated by the adoption of e-commerce studies on SMEs in Sleman Regency. This study uses a sample of 100 respondents from Prima Village SMEs who have used e-commerce. The sampling technique utilized in this examination is purposive sampling, and the information investigation technique utilized is Partial Least Square (PLS). The results of this study indicate that relative advantage, perceived ease of use, and perceived usefulness have a positive impact on e-commerce adoption. The relative advantage and adoption of e-commerce have an effect on marketing performance.